Analysis of B-cell immune tolerance induction using transgenic mice. - Ferry, H; Cornall, R (2004)
Over the past 15 yr, the use of transgenic mice has led to significant advances in our understanding of immunological tolerance. In a normal repertoire the number of B cells with a single antigen receptor specificity is very small, making the study of their fate difficult. In contrast, animals that carry transgenes encoding rearranged immunoglobulin genes generate large numbers of B cells that, by the process of allelic exclusion, have an identical specificity. Exploitation of this effect has enabled the mechanisms involved in B-cell tolerance to be explored in some detail. In this review we use the hen egg lysozyme (HEL) model system to illustrate the generation and preparation of a transgene. In our example, we describe the generation of mice expressing HEL as a systemic, intracellular, membrane-bound self-antigen. The same principles and methods apply to immunoglobulin transgenes. We briefly discuss the techniques that could be used to explore mechanisms of tolerance to systemic intracellular antigens in these mice.